Mentoring the Development of PAI Quality Assurance Modules Based on Local Wisdom at STAI Ibnurusyd Kotabumi - Safroni, Azmi; Suraji, Suraji; Rupiah, Rupiah; Fitriyani, Rika; Supriyanti, Supriyanti (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
This community service program aimed to improve lecturers’ competence in developing a local wisdom-based Islamic Religious Education (PAI) quality assurance module at STAI Ibnurusyd Kotabumi. The program employed a participatory mentoring approach involving 10 participants, consisting of PAI lecturers, the Quality Assurance Institute (LPM), study program leaders, and a local community representative. Activities were conducted through socialization, training, workshops, intensive mentoring, and evaluation, with data collected using participant observation, interviews, and document analysis, and analyzed qualitatively. The main problem addressed was the existing quality assurance module, which was normative, culturally non-contextual, and lacked operational quality indicators. The results showed an increase in lecturers’ conceptual understanding of local wisdom-based quality assurance, reflected in the successful formulation of contextual quality indicators integrating values of cooperation, deliberation, politeness, and religiosity. The main output of the program was a locally developed, wisdom-based PAI quality assurance module, validated by LPM. Practically, the module serves as an institutional reference for planning, implementing, and evaluating PAI learning, strengthens lecturers’ professionalism, and supports the development of a culturally responsive quality culture in Islamic higher education, particularly in the socio-cultural context of North Lampung.